Development and Reproducibility of a Computed Tomography–Based Measurement for Upper Body Subcutaneous Neck Fat - Rosenquist, Klara J. (J Am Heart Assoc, 2014)
BACKGROUND: Upper body subcutaneous neck fat (UBSF) is a unique fat depot anatomically separate from visceral abdominal fat that appears to be associated with cardiometabolic risk above and beyond generalized adiposity. We sought to develop a protocol to quantify UBSF using multidetector computed tomography measurements. METHODS AND RESULTS: Protocol development was performed in participants from the Framingham Heart Study who had participated in the multidetector computed tomography scanning substudy, consisting of chest scans. Volumetric assessment of UBSF was defined by 40 contiguous 0.625‐mm slices superior to the body of the sternum. The reader manually traced the chest to identify total neck fat. Breast tissue exterior to the chest wall was excluded. Subcutaneous and visceral fat volumes were obtained using standard protocols. Age‐ and sex‐adjusted Pearson correlation coefficients were used to assess the association among UBSF, traditional adiposity measures, and cardiometabolic risk factors. Inter‐ and intrareader reproducibility was assessed using intraclass correlation coefficients. Volumetric assessments were obtained in 92 participants because 8 scans were not readable (51% women; mean age: 59 years [women], 58 years [men]). The mean volume of UBSF was 310 cm(3) for women and 345 cm(3) for men. Intra‐ and interreader class correlation coefficients were 0.99 and 0.99, respectively. UBSF was correlated with waist circumference (r=0.90), neck circumference (r=0.75), body mass index (r=0.89), subcutaneous adipose tissue (r=0.87), and visceral adipose tissue (r=0.86). CONCLUSIONS: UBSF can be quantified reproducibly using computed tomography in a community‐dwelling sample from the Framingham Heart Study.